Calibration‐free pTx of the human heart at 7T via 3D universal pulses. Issue 1 (16th August 2021) - Aigner, Christoph Stefan; Dietrich, Sebastian; Schaeffter, Tobias; Schmitter, Sebastian
Abstract : Purpose: MRI at ultra‐high fields in the human body is highly challenging and requires lengthy calibration times to compensate for spatially heterogeneous B 1 + profiles. This study investigates the feasibility of using pre‐computed universal pulses for calibration‐free homogeneous 3D flip angle distribution in the human heart at 7T. Methods: Twenty‐two channel‐wise 3D B 1 + data sets were acquired under free‐breathing in 19 subjects to generate a library for an offline universal pulse (UP) design (group 1: 12 males [M] and 7 females [F], 21‐66 years, 19.8‐28.3 kg/m 2 ). Three of these subjects (2M/1F, 21‐33 years, 20.8‐23.6 kg/m 2 ) were re‐scanned on different days. A 4kT‐points UP optimized for the 22 channel‐wise 3D B 1 + data sets in group 1 (UP22‐4kT) is proposed and applied at 7T in 9 new and unseen subjects (group 2: 4M/5F, 25‐56 years, 19.5‐35.3 kg/m 2 ). Multiple tailored and universal static and dynamic parallel‐transmit (pTx) pulses were designed and evaluated for different permutations of the B 1 + data sets in group 1 and 2. Results: The proposed UP22‐4kT provides low B 1 + variation in all subjects, seen and unseen, without severe signal drops. Experimental data at 7T acquired with UP22‐4kT shows comparable image quality as data acquired with tailored‐4kT pulses and demonstrates successful calibration‐free pTx of the human heart. Conclusion: UP22‐4kT allows for calibration‐free homogeneous flip angle distributions across the human heart at 7T. Large inter‐subject variations because of sex, age, and body mass index are well tolerated. The proposed universal pulse removes the need for lengthy (10‐15 min) calibration scans and therefore has the potential to bring body imaging at 7T closer to the clinical application.